1995
DOI: 10.1111/j.1525-1594.1995.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

An Implantable Seal‐less Centrifugal Pump with Integrated Double‐Disk Motor

Abstract: Thrombus formation and sealing problems at the shaft as well as the compact and efficient design of the driving unit have been major difficulties in the construction of a long-term implantable centrifugal pump. To eliminate the problems of the seal, motor size, and efficiency, two major steps were taken by modifying the Vienna implantable centrifugal pump. First, a special driving unit was developed, in which the permanent magnets of the motor themselves are used for coupling the force into the rotor. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
(5 reference statements)
0
10
0
1
Order By: Relevance
“…This pump can provide 5 L/min against 120 mm Hg total pressure head at 2000 rpm. The normalized index of hemolysis (NIH) value of this pump was comparable to that of the BP-80 pump (BioMedics, Minneapolis, MN, U.S.A.) (10). The Gyro PI-601 was implanted as a right or left ventricular assist device in the preperitoneal space of five calves (14,15).…”
Section: Gyro C1e3 Centrifugal Blood Pump To Nedo Pi (Permanently Impmentioning
confidence: 90%
See 2 more Smart Citations
“…This pump can provide 5 L/min against 120 mm Hg total pressure head at 2000 rpm. The normalized index of hemolysis (NIH) value of this pump was comparable to that of the BP-80 pump (BioMedics, Minneapolis, MN, U.S.A.) (10). The Gyro PI-601 was implanted as a right or left ventricular assist device in the preperitoneal space of five calves (14,15).…”
Section: Gyro C1e3 Centrifugal Blood Pump To Nedo Pi (Permanently Impmentioning
confidence: 90%
“…28, No. 10,2004 analysis revealed that a washout flow was created between the bottom shaft and the bottom pivot bearing when the impeller was levitated. In addition, a levitated impeller has less platelet adhesion than when nonlevitated around the bottom pivot area behind the impeller (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The driver motor for the actuator is a brushless DC one with the coils fixed in a plastic mold and mounted on the circumference of the housing. This coil apparatus is placed between 2 rotating disks with permanent magnets that are mounted on 1 central axle (6). The motor is encapsulated in a titanium housing to guarantee hermetic sealing.…”
Section: Pump Head Actuator and Controllermentioning
confidence: 99%
“…Recently, rotary blood pumps have been achieving remarkable progress, as reported by many investigators (12)(13)(14)(15). We think that cost-effective and simple implantable nonpulsatile pumps will be developed in the near future as bridge-to-transplantation devices or as long-term VADs for clinical use,…”
mentioning
confidence: 99%